A Literature Reviews on the Dynamics of Leadership and Decision-Making in Groups: Insights into Collective Problem-Solving - Utami, Batina Yulia; Hadiyanto, Hadiyanto; Irsyad, Irsyad (Postgraduate School, Universitas Negeri Padang, 2024)
This literature review examines the dynamics of leadership and decision-making in groups, focusing on how collective problem-solving and shared responsibility influence organizational success. Using a library research methodology, this study synthesizes secondary data from books, peer-reviewed journals, and credible library resources. The methodological steps included data collection, critical evaluation, thematic analysis, and synthesis to derive relevant findings. The findings reveal that decision-making is a structured process involving logical considerations, alternative options, and clear goals. Group interactions significantly impact decision-making dynamics by encouraging conformity to group norms and influencing individual behaviors. However, challenges such as prolonged discussions, conformity pressure, and task ambiguity can hinder effective group decision-making. Additionally, decision types general decisions based on principles, and specific decisions tailored to unique situations require a balance between strategic frameworks and adaptability. This study underscores the importance of evidence-based approaches to understanding the complexities of leadership and group decision-making. Effective decision-making demands a comprehensive grasp of theories, group dynamics, and contextual influences. These insights are instrumental in fostering successful collaboration and optimizing decision-making in dynamic organizational environments.